What Unites Us All: Establishing Special Education Teacher Education Universals. (August 2016) - Darling, Sharon M.; Dukes, Charles; Hall, Kalynn
The theoretical base that supports human universals served as a model for proposing special education teacher education universals. The human universals model is explained and put forth as a basis for identifying special education teacher education universals. Twenty-four English language journals from different countries representing four continents were searched for special education teacher education universals, represented by four broadly defined categories: (a) policy, (b) practice, (c) pedagogy, and (d) teacher preparation/co-curricular activities. Each journal was searched from 2004 to 2015, and articles were coded using the aforementioned categories. Results indicated an overwhelming presence of teacher preparation/co-curricular descriptions, representing 51% of the total ( n = 815) articles categorized. The implications of these results are discussed in relation to defining and describing special education teacher preparation universals.